2019
DOI: 10.1259/bjr.20190572
|View full text |Cite
|
Sign up to set email alerts
|

Early clinical results of proton spatially fractionated GRID radiation therapy (SFGRT)

Abstract: Objective: Approximately 70 patients with large and bulky tumors refractory to prior treatments were treated with photon spatially fractionated GRID radiation (SFGRT). We identified 10 additional patients who clinically needed GRID but could not be treated with photons due to adjacent critical organs. We developed a proton SFGRT technique, and we report treatment of these 10 patients. Methods: Subject data were reviewed for clinical results and dosimetric data. 50% of the patients were metastatic at the time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 9 publications
0
22
0
1
Order By: Relevance
“…The treatment of 10 patients (large tumours) proton GRID therapy (1 cm-wide beams) with palliative intent has been reported (Ref. 31). The median time to last follow-up was around 6 months.…”
Section: Grid Therapymentioning
confidence: 99%
“…The treatment of 10 patients (large tumours) proton GRID therapy (1 cm-wide beams) with palliative intent has been reported (Ref. 31). The median time to last follow-up was around 6 months.…”
Section: Grid Therapymentioning
confidence: 99%
“…Indeed, ten patients with large tumors have already been treated with proton GRID therapy (1-cm wide beams) [34] with palliative intent. These patients had tumors that could not be treated with photons, standard broad-beam irradiation, or photon GRID due to the tolerance of normal tissues.…”
Section: Perspectives: Toward Clinical Trialsmentioning
confidence: 99%
“…En effet, dix patients atteints de tumeurs de grande taille ont déjà été traités par protonthérapie GRID (faisceaux de 1 cm de large) [34] dans un but palliatif. Ces patients avaient des tumeurs qui ne pouvaient pas être traitées avec des photons, une irradiation standard à large faisceau ou une GRID aux photons en raison de la tolérance des tissus normaux.…”
Section: Perspectives : Vers Les Essais Cliniquesunclassified
“…After initial studies over the years suggested that patients may benefit from GRID applications to their tumour, several new strategies for applying GRID with photons in IMRT treatment plans or with protons have emerged with advancing technological capabilities (36)(37)(38). These advanced GRID techniques allow for the delivery of spatial fractionation to deep seated bulky tumours and dose sparing to normal tissues.…”
Section: B J R U N C O R R E C T E D P R O O F Smentioning
confidence: 99%